DEVELOPMENT OF CURRICULUM BASED ON THE LOCAL WISDOM - Septiana Agustin (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study aims to develop the curriculum of Bejalen Public Elementary School in Semarang Regency based on the values of local wisdom. The development of this curriculum is based on the characters and resources in the local area, both natural and human resources. This type of research is descriptive qualitative with data collection techniques through observation, interviews, and FGD (Forum Group Discussion). Observations show that local areas have maritime potential as natural resources. Thus, most of the livelihoods of Bejalen Elementary School students are fishermen. The results of interviews with local residents include utilization of natural resources and empowerment of human resources. The results of the FGD with the local district staff members produced data that the local area had become one of the tourist areas in Semarang Regency called Pelangi Tourism Village. All of this data is the material for developing the curriculum of Bejalen Public Elementary School. The results of this study explain that the curriculum development of Bejalen Public Elementary School in Semarang Regency is based on the values of local wisdom which includes the cultivation of natural resources and the empowerment of human resources. The recommendation for further research is research on developing elementary school curriculum based on local wisdom in other schools.